1999
DOI: 10.1063/1.370554
|View full text |Cite
|
Sign up to set email alerts
|

An rf sustained argon and copper plasma for ionized physical vapor deposition of copper

Abstract: Langmuir probe, optical emission spectroscopy, and biased quartz crystal microbalance measurements were used to investigate an argon and copper plasma used for ionized physical vapor deposition of copper. Copper vapor generated by a magnetron sputter discharge is ionized upon passing through an argon discharge excited by an internal rf induction antenna. Argon plasma characteristics such as electron temperatures T e , plasma densities n e , and plasma and floating potentials V p and V f , were studied as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The plasma parameters and their dependence on rf power in an ICP-MS discharge have been measured by several groups [14,[48][49][50][51]. In general, it is found that the ionization, and therefore the ionization flux fraction, increases with increased rf power and pressure.…”
Section: Inductively Coupled Plasma Magnetron Sputtering (Icp-ms)mentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma parameters and their dependence on rf power in an ICP-MS discharge have been measured by several groups [14,[48][49][50][51]. In general, it is found that the ionization, and therefore the ionization flux fraction, increases with increased rf power and pressure.…”
Section: Inductively Coupled Plasma Magnetron Sputtering (Icp-ms)mentioning
confidence: 99%
“…In general, it is found that the ionization, and therefore the ionization flux fraction, increases with increased rf power and pressure. Wang et al [48,49] investigated the plasma parameters in an Ar discharge with a Cu target. Fig.…”
Section: Inductively Coupled Plasma Magnetron Sputtering (Icp-ms)mentioning
confidence: 99%
“…However, for our simulations we used conditions typical for deposition of copper which were used in the experiment in [3]. One of the main variables in this study was RF power.…”
Section: Global Model Resultsmentioning
confidence: 99%
“…Paper [2] described ionization up to 80% for aluminium atoms. Flux fraction of copper ions exceeding 40% was shown in [3]. Afterwards, the metal ions together with ions of the carrier gas move towards the negatively biased substrate.…”
Section: Introductionmentioning
confidence: 94%
“…At the high ICP power, re-sputtering from the surface of the ICP tube may occur. As mentioned above, a simple solution is that the RF coil of IPVD is made of the same one as the target material [13][14]. On the other hand, Imbert at al.…”
Section: Contamination Issue From Icp Tubementioning
confidence: 99%